Methamphetamine-Related Emergency Department Visits Requiring Psychiatric Admission: A Retrospective Cohort Study. - Bahji, Anees (International Journal of Mental Health & Addiction, 2021)
Objectives: The aim of this study was to determine if certain clinical or sociodemographic characteristics were associated with a higher likelihood of psychiatric admission for stimulant-related emergency department (ED) visits. Methods: Using administrative data collected by the Kingston Health Sciences Centre Emergency Department Information System was used to assemble a retrospective cohort study. The primary outcome measure was ED disposition (admission vs. discharge), while covariates included age, sex, primary ED diagnosis, mode of ED arrival, and length of ED stay. Statistical analysis was conducted using bivariate and multivariate logistic regression in SAS. Key Findings: Over a 4-year period, 915 stimulant-related presentations were recorded (64.5% male, mean age 32.8 years). Nearly 15% of all visits required psychiatric admission. Time trend analysis showed a significant increase in the number of visits by fiscal year. The most common stimulant-related presentations were stimulant intoxication (32.8%) and stimulant-induced psychosis (23.0%). Significant predictors of psychiatric admission were arrival by police (adjusted odds ratio [AOR] = 1.90), older age (AOR = 1.03), longer length of ED stay (AOR = 1.03), and more severe triage score (AOR = 0.4). Conclusions: Certain clinical and sociodemographic characteristics are associated with psychiatric admission among individuals who present to the ED with methamphetamine-related chief complaints. These characteristics could later be used to improve clinical risk profiles and ED triage algorithms that can help identify patients who may require enhanced community care and those who may benefit from psychiatric admission.